CITA-CITA MENUJU MASYARAKAT MADANI, MUNGKINKAH ? - Supriyatno, Arie (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2009)
The results of this thinking to try to offer new concepts of civil society in terms of: ontology, axiology, and epistemology. Ontologically, civil society is a democratic society. In axiology, civil society aims to reduce the demands for reform both from within and outside the country. In addition, through civil society will arise educational innovations. In epistemology, civil society achieved through short-term goals and long term through the democratization of education. With the democratization of education will be the equality between educators and learners in the teaching-learning process. Educational innovation contects democratization of education needs to address pragmatic issues so that students can not be separated from the culture and society.